Transcriptomic and metabolomic analysis of yellow leaf mutant variation in Taxus cuspidata - Zhang, Shuo; Liu, Duo; Zhang, Lihui; Zhang, Yanwen (Frontiers in Plant Science, 2025)
During the cultivation of Taxus cuspidata, significant differences in leaf coloration between different types have emerged, which is of great significance for variety breeding. This study employed transcriptomic and metabolomic analyzes to identify key genes and metabolites associated with leaf color variation between the yellow leaf type and the green leaf type. The results showed: (1) Metabolites such as kaempferol 3-p-coumaroylglucoside, quercetin-3’-glucuronide, kaempferol-3-O-rutinoside, Ridiculuflavone D, phaeophorbide b, and paclitaxel were significantly higher in the yellow leaf type compared to the green leaf type, while the content of tetrapyrrole compounds was significantly lower in the yellow leaf type.(2) Transcriptomic analysis indicated that genes involved in carotenoid synthesis, flavonoid synthesis, and chlorophyll degradation, such as F3H, FLS, ZEP, PSY, and FLN, were significantly upregulated in the yellow leaf type compared to the green leaf type. In contrast, genes involved in chlorophyll biosynthesis (GLK, SGR) and anthocyanin synthesis (DFR) were significantly downregulated. qRT-PCR analysis further validated these results. (3) Integrative transcriptomic and metabolomic analysis revealed significant positive correlations between F3H, FLS, FLN genes and flavonoid compounds, and between GLK, SGR genes and the reduction in tetrapyrrole compounds, promoting chlorophyll and chloroplast degradation. These findings suggest that the acquisition of yellow leaf traits in Taxus cuspidata is mainly achieved by enhancing upstream flavonoid biosynthesis pathways and downstream chlorophyll degradation pathways, including phenylpropanoid biosynthesis, flavonoid biosynthesis, and chlorophyll degradation, while limiting the downstream anthocyanin biosynthesis pathway and related processes.